2018
DOI: 10.1002/1873-3468.13103
|View full text |Cite
|
Sign up to set email alerts
|

The membrane‐bound O‐acyltransferase Ale1 transfers an acyl moiety to newly synthesized 2‐alkyl‐sn‐glycero‐3‐phosphocholine in yeast

Abstract: To elucidate the mechanism of acyl chain remodeling at the sn-1 position of phosphatidylcholine (PC), we investigated acyl chain introduction using a newly synthesized 1-hydroxy-2-hexadecyl-sn-glycero-3-phosphocholine (HHPC) in Saccharomyces cerevisiae. HHPC is incorporated into yeast cells and converted to a PC species containing acyl residues of 16 or 18 carbons. The efficiency of palmitoleic acid introduction to HHPCin vitro is lower in the reaction with the extract from the deletion mutant of ALE1, which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…With the fast development of organic synthetic chemistry, many natural lipids could be synthesized in the lab or even became commercially available, e.g., PC (phosphatidylcholine), PE (phosphatidylethanolamine), PS (phosphatidylserine). [47,48] Furthermore, some synthetic analogs of the natural lipids could also be designed to bring more potential novel properties, e.g., hexadecyl phosphocholine, [49] 18:1 MPB PE (1,2-dioleoyl-sn-glycero-3-phosphoethanolamine-N-[4-(p-maleimidophenyl) butyramide]). [50] Due to the controllable membrane composition, synthetic/artificial phospholipid membrane has been widely studied and employed to construct artificial membranes close to natural cell membranes.…”
Section: Artificial Amphiphilic Membranesmentioning
confidence: 99%
“…With the fast development of organic synthetic chemistry, many natural lipids could be synthesized in the lab or even became commercially available, e.g., PC (phosphatidylcholine), PE (phosphatidylethanolamine), PS (phosphatidylserine). [47,48] Furthermore, some synthetic analogs of the natural lipids could also be designed to bring more potential novel properties, e.g., hexadecyl phosphocholine, [49] 18:1 MPB PE (1,2-dioleoyl-sn-glycero-3-phosphoethanolamine-N-[4-(p-maleimidophenyl) butyramide]). [50] Due to the controllable membrane composition, synthetic/artificial phospholipid membrane has been widely studied and employed to construct artificial membranes close to natural cell membranes.…”
Section: Artificial Amphiphilic Membranesmentioning
confidence: 99%
“…When provided with acyl receptors such as lysophosphatidic acid, lysophosphatidylcholine (LPC), lysophosphatidylethanolamine, lysophosphatidylglycerol, lysophosphatidylinositol and lysophosphatidylserine, the LPCAT activity of ALE1 knockout mutants diminishes to 28% of that observed in wild strains, whereas the activity of other acyltransferases only experiences comparatively minor reduction [23]. Combined with our lipidomics data, we therefore consider that the principal function of ALE1 in yeast revolves the conversion of lysophosphatidylcholine to PC [23,24]. We quantified the three most abundant phosphatidylcholines in yeast and found that only DPPC increased under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…PE has a conical head group, which could increase the negative membrane curvature (52). PC always contains an unsaturated acyl chain, which contributes to the increase of membrane fluidity (53). Despite their low abundance, PS and PI play important roles in balancing the membrane surface charge (54,55).…”
Section: Discussionmentioning
confidence: 99%